Tissue healing efficacy in burn patients treated with 1% silver sulfadiazine versus other treatments: a systematic review and meta-analysis of randomized controlled trials - Alex Bezerra da Silva Maciel; Josmar França Ortiz; Beatriz Santos Siqueira; Gabriela Ferreira Zanette (Sociedade Brasileira de Dermatologia, 2019)
Abstract This study aims to evaluate tissue healing efficacy in burn patients treated with 1% silver sulfadiazine versus other treatments. This is a systematic literature review and meta-analysis of randomized clinical trials performed according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA) and PICO strategy, registered in the International Prospective Register of Systematic Reviews (PROSPERO) under the number CRD42017081057. The review found 71 studies in MEDLINE/Pubmed, 1 in Clinical Trials, 19 in the Cochrane Library, and 4 in LILACS in five manual searches. Of these, 81 studies were pre-selected. After independent analysis by two reviewers, only 11 studies met the inclusion criteria for the review. All studies (n = 11) using alternative treatments to silver sulfadiazine were shown to be superior in the mean time for complete wound healing, with statistically significant differences between experimental and control groups (p <0.00001); mean difference (- 4.26), 95% CI [- 5.96, - 2.56].